PENGARUH UKURAN PERUSAHAAN, STRUKTUR ASET, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA BUMN YANG GO PUBLIC DI BURSA EFEK INDONESIA - zainul, zaida rizqi; Pintariang, Iis Alfanias (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2020)
This study aims to determine the effect of firm size, asset structure and profitability on capital structure of SOEs that go public on Indonesia Stock Exchange (IDX). This study uses panel data with 16 state-owned companies that go public on Indonesia Stock Exchange from 2013-2017 period. The analytical method used is multiple regression analysis with a random effect model. The results of study show that: 1) size of the company has a positive and not significant effect on capital structure. 2) asset structure has a positive and significant effect on capital structure. 3) Profitability has a negative and significant effect on capital structure. Therefore SOEs can consider asset structure and profitability in making funding decisions.